Effect of Medical Rehabilitation Services on Pain Intensity in Low Back Pain Patients - Imran Safei; Zulfahmidah Zulfahmidah; Kasmawati Kasmawati (UMI Medical Journal, 2023)
Background: Low back pain is a symptom that is not directly related to mortality but is a cause of morbidity. The incidence of LBP was reviewed based on patient visits to several hospitals in Indonesia, ranging from 3-17%. The purpose of this research is to Effect of Medical Rehabilitation Services on Pain Intensity in Low Back Pain Patients. Method: This type of research includes quantitative research with a cross sectional approach. Data collection is done through medical records. The research sample was all patients diagnosed with low back pain who were treated at the medical rehabilitation polyclinic at the Ibnu Sina Makassar Hospital within 4 years (2019-2022). Data analysis was carried out, namely univariate and bivariate analysis using the Paired t-test. Results: The research results obtained 31 samples that met the inclusion criteria and showed that there was an effect of medical rehabilitation on reducing the low back pain scale in patients with low back pain (p=0.00). Conclusion: There is an effect of medical rehabilitation on decreasing the low back pain scale in patients with low back pain. Keywords: Low; medical rehabilitation; pain intensity